Physical activity and factors associated with the costs of low back pain among adults after 18 months of follow-up: a cohort study - Zanuto, Everton Alex Carvalho [UNESP]; Penna, Valter; Rocha da Silva, Cristiano; Ronque, Enio Ricardo Vaz; Negrão Filho, Ruben de Faria [UNESP]; Castoldi, Robson Chacon [UNESP]; Codogno, Jamile Sanches [UNESP]; Fernandes, Rômulo Araújo [UNESP] (FapUNIFESP (SciELO), 2025)
BACKGROUND: Chronic low back pain (CLBP) is a substantial health problem that causes considerable economic losses. Several studies have demonstrated the protective effect of habitual physical activity; however, little data are available regarding its impact on the costs associated with CLBP. OBJECTIVE: The primary aim of this study was to analyze the costs of CLBP in the Brazilian Health System and associated factors among adults. DESIGN AND SETTING: An 18-month cohort study was conducted in two basic health units in Presidente Prudente (SP), Brazil. METHODS: A total of 198 patients were interviewed and evaluated four times: at baseline, with retrospective data covering the previous 12 months, and at six, 12, and 18 months. The Nordic and Baecke questionnaires were used to classify CLBP, and the Baecke questionnaire was used for physical activity assessment. The costs were calculated by reviewing the demand for services from medical records. Body mass index (kg/m2) was determined using body mass and height values collected during the interviews. The questionnaire included confounding variables, such as sex, age, ethnicity, and socioeconomic status. RESULTS: A high prevalence of CLBP was observed, which was associated with female sex and younger age. CLBP resulted in high costs for medical consultations (without: US$ 34.25 ± 23.21; with: US$ 39.62 ± 27.25; P = 0.049), while cycling was negatively associated with costs (rho =-0.289; P = 0.049). CONCLUSION: Lower back pain was associated with higher costs of medical consultations, while cycling was associated with reduced costs.
Keywords: Backaches; Body composition; Costs control; Costs of health; Economics; Exercise; Physical exercise; Prevention and control [subheding]; Public health administration; Surveys and Questionnaires